Which way to food security in East Africa? Future scenarios in a changing climate - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
What does the future hold for food security in East Africa? How do uncertain future socio-economic developments change East Africa's capacity for climate adaptation and mitigation? https://ccafs.cgiar.org/scenarios Together with regional stakeholders, the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) is exploring how different political and socio-economic futures for East Africa may affect food security and environmental change in the region, and how this may affect the region's vulnerability to future climate change. Audio and initial editing by PANOS East Africa Camera: Roland Kokasi Odinga Script: Joost Vervoort Video Editor: Jacob Njoroge Narration: Rachael Takali Producer: Roland Kokasi Roland Technical Supervisor: Lynn Najjemba Overall Supervisor: Okubal Peter James Ejokuo Final edit by Elisabeth van de Grift